2019
DOI: 10.1002/ar.24250
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of the Human Tibial and Peroneal Nerves Following Stretch With Histological Correlations

Abstract: Despite the extensive literature regarding peripheral nerve stretch injuries, there are few studies that compare the nerve histology with the mechanical properties in humans. There is clinical evidence suggesting that the peroneal nerve is at greater risk for injury compared to the tibial nerve following total hip arthroplasty and hip trauma. We examined the two nerves from fresh human cadavers with or without controlled stretch. The mechanical properties, stiffness, and strain were compared with light microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
(49 reference statements)
1
24
0
1
Order By: Relevance
“…The longitudinal displacement of the median nerve in the forearm was 2.3 mm when cervical lateral flexion was applied [ 27 ]. Movement of the joint can modify the elasticity property of the median nerve when enough mechanical stress is applied to it [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal displacement of the median nerve in the forearm was 2.3 mm when cervical lateral flexion was applied [ 27 ]. Movement of the joint can modify the elasticity property of the median nerve when enough mechanical stress is applied to it [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Peripheral nerves have a wavy, undulating structure that allows for some degree of physiological stretch. 1 38 39 Using human cadaveric tissue, Kerns et al 39 reported differences in undulations patterns at failure between tibial and peroneal nerves. The significantly lower failure stress seen in BP nerve when compared with tibial nerve, in this study, suggests that the BP nerve may have fiber orientations that present a biomechanical disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although we could have easily applied our crush model to determine these lesion-specific threshold parameters, we chose not to ascertain them due to certain fundamental impediments which diminish the clinical relevancy and application of the results. For instance, determination of these parameters using a rat model alone is in itself a fundamental limitation because the extent of protection afforded by the nerve epineurium varies according to species being investigated and is greater in humans than in rats (Kerns, 2008 ; Alvites et al, 2018 ; Kerns et al, 2019 ). Threshold parameters also vary based on the specific nerve being investigated and on its anatomical location, with crushing parameters likely being greater at or near joints (Alvites et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%